Can We Predict Feto-Maternal Adverse Outcomes of Vacuum Extraction? - Cohen, Gal; Schreiber, Hanoch; Shalev Ram, Hila; Ovadia, Michal; Shechter-Maor, Gil; Biron-Shental, Tal (Geburtshilfe und Frauenheilkunde, 2022)
Introduction Vacuum extraction (VE) is an important modality in modern obstetrics, yet sometimes results in maternal or neonatal adverse outcomes, which can cause a lifetime disability. We aimed to characterize potential risk factors for adverse outcomes that in retrospect would have led the physician to avoid the procedure.Materials and Methods Retrospective cohort of 3331 singleton pregnancies, ≥ 34 w delivered by VE. 263 deliveries (7.9%) incurred a VE-related feto-maternal adverse outcome, defined as one or more of the following: 3–4th-degree perineal laceration, subgaleal hematoma, intracranial hemorrhage, shoulder dystocia, clavicular fracture, Erb’s palsy or fracture of humerus. 3068 deliveries (92.1%) did not have VE-related adverse outcomes. Both groups were compared to determine potential risk factors for VE adverse outcomes.Results Multivariable regression found seven independent risk factors for VE-related feto-maternal adverse outcomes: Nulliparity – with an odds ratio (OR) of 1.82 (95% CI = 1.11–2.98, p = 0.018), epidural anesthesia (OR 1.99, CI = 1.42–2.80, p < 0.001), Ventouse-Mityvac (VM) cup (OR 1.86, CI = 1.35–2.54, p < 0.001), prolonged second stage as indication for VE (OR 1.54, CI = 1.11–2.15, p = 0.010), cup detachment (OR 1.66, CI = 1.18–2.34, p = 0.004), increasing procedure duration (OR 1.07 for every additional minute, CI = 1.03–1.11, p < 0.001) and increasing neonatal birthweight (OR 3.42 for every additional kg, CI = 2.33–5.02, p < 0.001). Occiput anterior (OA) position was a protective factor (OR 0.62, CI = 0.43–0.89, p = 0.010).Conclusions VE-related adverse outcomes can be correlated to clinical characteristics, such as nulliparity, epidural anesthesia, VM cup, prolonged second stage as indication for VE, cup detachment, prolonged procedure duration and increasing neonatal weight. OA position was a protective factor. This information may assist medical staff to make an informed decision whether to choose VE or cesarean delivery (CD).
Keywords: Vakuumentbindung; Vakuumextraktion; vakuumbedingte unerwünschte Outcomes; vakuumbedingte mütterliche Komplikationen; vakuumbedingte neonatale Komplikationen